INFLUENCE COMPENSATION, DISCIPLINE WORK AND ETHICS WORK ON THE PERFORMANCE OF BPJS EMPLOYEE EMPLOYEES NORTH MEDAN BRANCH - Fanny Ismaliah; Ahmad Azmi; Saimara A.M Sebayang (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Study This aim For know How influence compensation, discipline Work And ethics Work gasped performance employee BPJS Employment Branch Medan North. Study This use methodology quantitative. Method This use Sampling fed up technique This is determination sampleif all member population is used as sample . Sampling fed up This oftencarried out if the population is relatively small, less than 30 people, or the research is want to make generalization with very small errors and research has samples 35. Engineering collecting data using a questionnaire (Questionnaire). The research results show that compensation, work discipline and work ethics are partial And simultaneous influential positive And significant to performance employee BPJS North Medan branch employment. There is a strong correlation between compensation, work discipline and work ethics with employee performance and the percentage size, namely 48.5% and the rest 51.5% can explained by variable other Which not researched.